Persepsi Spiritualitas pada Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisa - Giat Wantoro; Yuliana Yuliana (Prosiding Seminar Kesehatan Nasional, 2022)
Spirituality is something that believes by someone in relation to a higher power (The Almighty God), that raises a need and love, affection for god, and apology for every mistake that has been made. Spirituality gives an important role in thinking and behaving for chronic kidney failure patients who are undergoing hemodialysis. Spirituality is beneficial to recognize that patients have power and spiritual beliefs where the nurse can be used as the source to help patients undergo a more healthy life, the source of power, and disease cure. The aim of this study is known the description of spirituality perception in chronic kidney failure patients who are undergoing hemodialysis at the Pertamedika Baiturrahim Jambi Hospital. This is a quantitative study that used a descriptive research method. The population in this study is all chronic kidney failure patients who are undergoing Hemodialysis at Pertamedika Baiturrahim Jambi Hospital in October 2021 totaling 90 respondents. The research instrument used is the Daily Spiritual Experience Scale (DSES) and analyzed univariately. The result of this spirituality perception study in chronic kidney failure patients undergoing Hemodialysis at Pertamedika Baiturrahim Jambi Hospital showed (82.1%) have a high spirituality perception and (17.9%) have a medium spirituality perception. It can be concluded that the higher the spirituality perception of respondents, the higher the spirituality level of the respondents. Hopefully from the result of this study to the hospital’s party especially the nurse can give support and further enhance the motivation of patients to heal and the nurse is expected to provide nursing care with an approach (Spiritual care).